Assessing Australian consumer preferences for fresh pork meat attributes: A best-worst approach on 46 attributes. (November 2022) - Duong, Chien; Sung, Billy; Lee, Sean; Easton, Julia
Abstract: Constant competition and changing consumer preferences prompts the need to improve the competitiveness of the Australian pork industry. This study examines the heterogeneity of Australian consumer preferences related to fresh pork cues. Using best–worst scaling, we examine the importance of 15 intrinsic and 31 extrinsic product attributes to 196 Australian consumers. Findings reveal that taste, succulence and the smell of boar taint were the most important intrinsic cues, while animal welfare and naturalness were the most important extrinsic cues. Based on the importance of intrinsic cues, four segments were identified, namely boar taint haters, lean meat eaters, colour lovers and cuts and size matters . Four segments based on extrinsic cues were identified as animal and environment lovers, naturalness lovers, demanding buyers and utilitarian buyers . This study contributes significantly to the industry by offering granular insights with respect to Australian consumer demands and optimal communication of cues. Highlights: Using best-worst scaling to examine up to 46 product attributes in relation to fresh pork meat consumption in Australia. Taste, succulence, and no smell of boar taint are key eating-quality indicators. Australia consumers value fresh pork meat with high level of animal welfare and naturalness. Four intrinsic segments include boar taint haters, lean meat eaters, colour lovers, and cuts & size matters. Four extrinsic segments include animal & environment lovers, naturalness lovers, demanding buyers, and utilitarian buyers.